Consumer Behavior as a Determinant Factor of E-Commerce Development in Cameroon - Zoa BItjoka Jacques Ivan (International Journal of Engineering and Management Research, 2019)
The coming of electronic commerce to Cameroon, which is an internet way of doing transactions and provision of goods and services to customers, has spruced up the way people do things in this country. Businesses and people are now entitled to get engaged into this way of doing transactions, which is becoming more and more popular among the Cameroonians recently. Many old firms and companies are now trying day after day to reach their customers through this new way of doing things. While on the other hand, there are new businesses which are fully relying on electronic commerce to be able to function and they gradually keep gaining importance into the Cameroonians daily practices. On the other hand, we were eager to find out if the Cameroonian population, all ages, gender, profession, level of education and more are interested in this new form of business that in some way or the other changes their daily practices and even beliefs. The major objective of the study was to find out how these Cameroonians react to and take this business, if they are already used to it and what needs to be improved. This study was made with a survey design in order to collect data from respondents and a random sampling procedure was used to represent the entire population. The research established that a good number of Cameroonians were adopting electronic commerce for their online transactions like buying of goods and services and an increase in the trust.